Identification of more than 100 structurally unique DNA-phosphate adducts formed during rat lung carcinogenesis by the tobacco-specific nitrosamine 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone. (29th November 2017) - Ma, Bin; Zarth, Adam T; Carlson, Erik S; Villalta, Peter W; Upadhyaya, Pramod; Stepanov, Irina; Hecht, Stephen S
Abstract : We characterized a panel of 107 structurally distinct pyridylhydroxybutyl DNA phosphate adducts in lung tissues of rats treated chronically with the tobacco-specific lung carcinogen 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK). These newly identified adducts could be used as biomarkers in future studies of tobacco carcinogenesis. Abstract: The tobacco-specific nitrosamine 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK) is a powerful lung carcinogen in animal models and is considered a causative factor for lung cancer in people who use tobacco products. NNK undergoes metabolic activation—a critical step in its mechanism of carcinogenesis—to an intermediate which reacts with DNA to form pyridyloxobutyl DNA base and phosphate adducts. Another important metabolic pathway of NNK is its conversion to 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanol (NNAL), which similarly forms pyridylhydroxybutyl DNA base adducts that have been characterized previously. In this study, we investigated the potential formation of pyridylhydroxybutyl DNA phosphate adducts. We report the characterization and quantitation of 107 structurally unique pyridylhydroxybutyl DNA phosphate adducts in the lungs of rats treated chronically with a carcinogenic dose of 5 ppm of NNK in their drinking water for up to 70 weeks, by using a novel liquid chromatography-nanoelectrospray ionization-high-resolution tandem mass spectrometry method. Our findings demonstrate that pyridylhydroxybutyl phosphate adducts account for 38–55 and 34–40% of all the measured pyridine-containing DNA adducts in rat lung and liver, respectively, upon treatment with NNK. Some of the pyridylhydroxybutyl DNA phosphate adducts persisted in both tissues for over 70 weeks, suggesting that they could be potential biomarkers of chronic exposure to NNK and NNAL. This study provides comprehensive characterization and relative quantitation of a panel of NNK/NNAL-derived DNA phosphate adducts, thus identifying NNK as the source of the most structurally diverse set of DNA adducts identified to date from any carcinogen.